2022
DOI: 10.1007/s40534-021-00267-6
|View full text |Cite
|
Sign up to set email alerts
|

Recycled materials in railroad substructure: an energy perspective

Abstract: Given that the current ballasted tracks in Australia may not be able to support faster and significantly heavier freight trains as planned for the future, the imminent need for innovative and sustainable ballasted tracks for transport infrastructure is crucial. Over the past two decades, a number of studies have been conducted by the researchers of Transport Research Centre (TRC) at the University of Technology Sydney (UTS) to investigate the ability of recycled rubber mats, as well as waste tyre cells and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Regarding the sub-ballast layer, the literature shows that sustainable solutions are related to the use of the following: non-conventional bituminous mixtures made with recycled materials [6], which are able to ensure great layer stability; and geocell-reinforced coal mine overburden waste materials [46], which have been proved to ensure a decrease in vertical settlements, lateral deformations, and subgrade stresses. A recent study [47] demonstrated that the use of recycled rubber products, such as CWRC mixtures (i.e., mixtures of coal wash (CW) and rubber crumbs (RC)) and SEAL mixtures (i.e., mixtures of steel furnace slag, CW and RC), to replace sub-ballast, tire cell reinforcements for sub-ballast and under-ballast mats increases the energy dissipation effect of the track, hence reducing the ballast degradation efficiently and increasing the track stability.…”
Section: Sub-ballastmentioning
confidence: 98%
“…Regarding the sub-ballast layer, the literature shows that sustainable solutions are related to the use of the following: non-conventional bituminous mixtures made with recycled materials [6], which are able to ensure great layer stability; and geocell-reinforced coal mine overburden waste materials [46], which have been proved to ensure a decrease in vertical settlements, lateral deformations, and subgrade stresses. A recent study [47] demonstrated that the use of recycled rubber products, such as CWRC mixtures (i.e., mixtures of coal wash (CW) and rubber crumbs (RC)) and SEAL mixtures (i.e., mixtures of steel furnace slag, CW and RC), to replace sub-ballast, tire cell reinforcements for sub-ballast and under-ballast mats increases the energy dissipation effect of the track, hence reducing the ballast degradation efficiently and increasing the track stability.…”
Section: Sub-ballastmentioning
confidence: 98%
“…Global experiences demonstrated that the construction of sub-ballast [ 20 , 21 ] is a strategic solution for high-speed and high-capacity lines [ 11 , 22 , 23 ], although it has higher environmental and economic costs [ 24 , 25 ]. In the last few years, extensive efforts to address environmental protection led to the adoption of low-impact mixing and laying technologies and to the use of secondary and/or high-performance raw materials, low-temperature asphalt mixtures, modified bitumen, and high-performance additives [ 26 , 27 , 28 , 29 , 30 ]. In particular, mixtures modified with rubber and polymer returned interesting results in terms of fatigue resistance [ 31 , 32 ], mechanical properties [ 33 , 34 ], and damping vibrations [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the construction/demolition wastes used in these applications is waste ballast (WB). A large amount of WB is formed due to the increasing need for new infrastructure along with developing rail track technology [ 40 ]. For example, Indian railways supplied around eight million cubic meters of ballast in 2017–2018 [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%